Pengaruh Media Leaflet Terhadap Faktor Aktivitas Fisik Dan Dampak Dengan Kejadian Obesitas Pada Remaja Di SMAN 1 PEDES - Khoerunnisa, Salma; Rizki, Linda (Universitas Pahlawan Tuanku Tambusai, 2024)
Obesity is one of the problems that most people in today's society ignore. Obesity is defined as abnormal fat or excessive fat riskier. The study used a pre-experimental method by giving a questionnaire on sman 1 pedes. Based on the results of all previous knowledge, education that used pre-test 52.33 received significantly higher results after it was established, namely, a post test score of 90.7. Increased knowledge is statistically meaningful (p< 0.05). It is concluded that there was a significant relationship between education and subsequent education.